Emerging Roles for Noncanonical NF-κB Signaling in the Modulation of Inflammatory Bowel Disease Pathobiology. Issue 9 (September 2016) - McDaniel, Dylan K.; Eden, Kristin; Ringel, Veronica M.; Allen, Irving C.
Abstract : Abstract: Crohn's disease and ulcerative colitis are common and debilitating manifestations of inflammatory bowel disease (IBD). IBD is characterized by a radical imbalance in the activation of proinflammatory and anti-inflammatory signaling pathways in the gut. These pathways are controlled by NF-κB, which is a master regulator of gene transcription. In IBD patients, NF-κB signaling is often dysregulated resulting in overzealous inflammation. NF-κB activation occurs through 2 distinct pathways, defined as either canonical or noncanonical. Canonical NF-κB pathway activation is well studied in IBD and is associated with the rapid, acute production of diverse proinflammatory mediators, such as COX-2, IL-1β, and IL-6. In contrast to the canonical pathway, the noncanonical or "alternative" NF-κB signaling cascade is tightly regulated and is responsible for the production of highly specific chemokines that tend to be associated with less acute, chronic inflammation. There is a relative paucity of literature regarding all aspects of noncanonical NF-ĸB signaling. However, it is clear that this alternative signaling pathway plays a considerable role in maintaining immune system homeostasis and likely contributes significantly to the chronic inflammation underlying IBD. Noncanonical NF-κB signaling may represent a promising new direction in the search for therapeutic targets and biomarkers associated with IBD. However, significant mechanistic insight is still required to translate the current basic science findings into effective therapeutic strategies. Abstract : Article first published online 9 August 2016.